Vegetation history and climate of the last 15,000 years at Laghi di Monticchio, southern Italy - Watts, W A; Allen, J R M; Huntley, B; Fritz, S C (Quaternary Science Reviews, 1996)
In southern It;aly, vegetation contemporary with the end of the last glacial maximum, from 15,000 to 12,000 years ago, is shown by pollen-analysis to have been treeless and steppe-like in character. At 12,500 BP (years before present), Betula (birch) expanded into the steppe, quickly followed by Quercus (oak), Fugus (beech), Tilia (lime) and other tree genera of mesic forest. High percentages of lUia point to a rich mesic forest that was contemporary with the ‘Allerod’ intersta- dial of northern Europe. A major decline in mesic trees with an accompanying return of Beth and steppe genera dated to 10,500 years ago identifies a ‘Younger Dryns’ climatic reversal. Betula and steppe genera were replaced by forest of Quercus and other mesic trees, notably Ulmus (elm), as the Holocene began. In the later Holocene, ca. 4000 years ago, Abies (fir), Curpinus betulus (hom- beam) and Taxus (yew) appeared. Abies and Tuxus became extinct locally about 2500 years ago, either because of climatic change, or perhaps because of the effects of early agriculture. The Full- glacial climate is thought to have been cold and summer-dry with mainly winter precipitation. The Lateglacial ‘Boiling-Allereld’ Interstadial was summer-wet and warm. The response-surface based climate reconstruction indi’zates an early Holocene climate with markedly colder winter conditions than today, about -5°C compared with 3.9-C today as a mean temperature for the coldest month. The annual temperature sum is reconstructed as somewhat higher than today, 3500 degree days as compared with a calculated value of 2900 for today. The later Holocene had a climate like today’s, Rainfall, and variation in iis seasonal distribution, has been a critical determinant of the vegetation cover. The fossil pollen record at Laghi Di Monticchio has been complemented by diatom and plant macrofossil studies which provide evidence of former lake environments as well as data on the upland forest. Lake levels remained high during the Full- and Lateglacial with encroachment of shore vegetation during th,e Holocene. The sediments also have an exceptionally rich record of tephra falls which are of importance in dating and core correlation. Twenty-one macroscopically visible tephras occur in sediments of the last 15,000 years
Keywords: climate reconstruction; FOREST; Holocene (voyant); Pollen analysis; vegetation history